Second Life Environment a planning and project platform in Regional Development - Karl Maack; Thomas Hedner; Adli Abouzeedan (European Regional Science Association (ERSA), 2010)
Second Life (SL) is a virtual "world" accessible via the Internet which enables its users, called Residents, to interact with each other through virtual characters, called "avatars". The residents can explore the SL hypothetical world, and participate in individual and group activities. Most importantly, they SL residents can create, trade and develop virtual property and its related services in a theoretical and experimental way. Thus, the SL concept is a three-dimensional modeling tool which can be used to model and assess regional developmental solutions. The SL concept allows a wide range of actors such as individuals, organizations and institutions to analyze projected solutions for their development ideas, schemes and solutions. In this paper we provide examples and discuss how specific institutions such as Universities have utilized SL platforms in its development planning of physical entities, curricula, public relations, openess as well as other dimensions and events. Also, we discuss the possibilities and limitations to use SL to develop and test ideas of regional development, without taking the costs and time of real world development and application.
Keywords: 330; Second life; regional development; virtual; physical; planning; applications